UPAYA MENINGKATKAN PARTISIPASI AKTIF SISWA PADA MATA PELAJARAN IPS MELALUI METODE ROLE PLAYING DI KELAS IV SEKOLAH DASAR - Putri Nur Fadhilah; Indah Wardatussa’idah; Mahmud Yunus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to increase students' active participation in social studies learning through the application of the Role Playing method to class IV-A students of SDN Pengadegan 03. The study used a Classroom Action Research (CAR) approach consisting of two cycles, each cycle including planning, implementation, observation, and reflection. Data were obtained through observation of students' active participation using observation sheets with indicators including the courage to ask questions, answer questions, group discussions, play roles, and cooperation during learning. The results showed that the application of the Role Playing method can significantly increase students' active participation. In the pre-cycle, active participation only reached 40%. After the action in cycle I, the figure increased to 75%. In cycle II, active participation reached 91%, exceeding the research success indicator of ≥85%.